EFFECTIVENESS OF IMPLEMENTATION TO ISO QUALITY MANAGEMENT SYSTEM : Case Study of ISO QMS 9001:2008 Policy Implementation at UIN Maulana Malik Ibrahim Malang - Asy'ari, Hasyim (2013)
ISO QMS as quality assurance is an international standard for quality system that uses certain clauses to give excellent services through continuous quality improvement resulting from self-learning processes in institutional management. This research focuses on analysis of the effectiveness of the implementation of QMS policy at UIN Maulana Malik Ibrahim (Maliki) Malang. Research questions are: How is the effectiveness of the QMS implementation? What are benefits and impacts of QMS implementation? What are strategic factors that influence the QMS implementation? And what solutions are effective to induce quality improvement at UIN Maliki Malang? This research uses a qualitative approach, with interview, documentation and observation techniques to invent and collect data. The unit analysis of this research is UIN Maliki Malang as an institution. The research subjects are leaders at all levels: rector, deans, directors, heads of programs, staffs, lectures and students. Steps in this research consist of observation to determine research targets, interviews, data recording, data collection, data classification, data analysis and report writing. The result of this research shows that the UIN leaders and internal stakeholders attempt to realize the clauses of QMS as shown at high SPM achievement during 2008-2010. Benefits of QMS implementation are inter alia job activities are planned and well organized; the institution has a systematic SOP; to induce lecturers and staff to perform more discipline and responsible; to facilitate accreditation process; readier documentation; lecturers' self-confidence improvement; to induce consciousness to continuous improvement of all aspects; give a basis to TQM program. The impact of the QMS implementation is the improvement in individual and institutional performance; cultural change in students' learning, teaching, staff working, and research; innovation and creativity improvement for institution, and institutional competitiveness and social image improvement. This research recommends that the leaders need to redesign SPM based on core duty and function, strategic vision and SPMPT to become the "Center of Excellence" and World Class University; to make extraordinary policy regarding human resource and budget availability; civitas academica should show continuous commitment and support to QMS implementation. Keywords: Policy Implementation, Quality Assurance, ISO QMS. SMM ISO sebagai penjaminan mutu merupakan standar internasional untuk sistem mutu yang menggunakan persyaratan tertentu untuk memberikan layanan terbaik dengan upaya-upaya perbaikan mutu berkelanjutan sebagai hasil proses pembelajaran diri dalam mengelola institusi. Riset ini difokuskan pada analisis efektivitas kebijakan implementasi SMM ISO di UIN Maulana Malik Ibrahim (Maliki) Malang. Pertanyaan penelitian adalah: Bagaimana efektivitas implementasi SMM? Apa saja manfaat dan dampak implementasi SMM? Faktor-faktor strategis apa saja yang mempengaruhi? dan solusi efektif apa saja untuk mempercepat peningkatan mutu UIN Maliki Malang? Pendekatan penelitian yang digunakan adalah penelitian kualitatif dengan teknik pengumpulan data berupa wawancara, studi dokumen dan observasi. Unit analisis penelitian adalah UIN Maliki Malang. Subjek penelitian terdiri atas para pimpinan institusi yakni rektor, pembantu rektor, dekan, direktur, ketua jurusan, ketua KJM, ketua lembaga penelitian, ketua lembaga pengabdian masyarakat, ketua BEM, dosen, karyawan dan mahasiswa. Langkah-langkah dalam penelitian meliputi penentuan seting lapangan, pengumpulan data, klasifikasi data, analisis data dan penulisan laporan. Hasil penelitian memberikan gambaran antara lain bahwa pimpinan dan stakeholder internal UIN telah berupaya menerapkan klausul-klausul SMM secara benar dan konsisten dalam bentuk pencapaian Standar Pelayanan Minimal (SPM) tahun 2008-2010 yang relatif tinggi. Manfaat penerapan SMM di UIN antara lain adalah aktivitas pekerjaan menjadi lebih tertata dan lebih teratur; institusi memiliki prosedur yang sistematis; mendorong para dosen dan karyawan bekerja lebih disiplin dan bertanggung jawab; memudahkan proses akreditasi; dokumentasi kegiatan lebih siap; mendorong kesadaran perlunya peningkatan mutu berkelanjutan; menjadi fondasi untuk menerapkan TQM. Sedangkan dampak penerapan SMM adalah meningkatnya kinerja individu dan institusi; meningkatnya rasa percaya diri dosen; meningkatnya kepuasan mahasiswa; terjadinya perubahan budaya belajar, budaya mengajar para dosen, budaya kerja karyawan, budaya penelitian; meningkatnya kemampuan inovasi dan kreativitas institusi; dan meningkatnya citra dan daya saing institusi. Pimpinan UIN Maliki Malang perlu menyusun kembali Standar Pelayanan Minimal (SPM) atas dasar pendekatan tupoksi, visi strategis dan SPMPT untuk menjadi "Center of Excellence"dan"World Class University"; Perlu kebijakan khusus terkait penyediaan SDM dan anggaran yang memadai; sivitas akademika perlu terus menunjukkan komitmen dan dukungan terkait implementasi SMM untuk memperbaiki mutu pembelajaran dan mutu institusi. Kata Kunci: Implementasi Kebijakan, Sistem Penjaminan Mutu, SMM ISO.